Environmental concentration of methamphetamine induces pathological changes in brown trout (Salmo trutta fario) - Sancho Santos, Maria Eugenia; Grabicová, Kateřina; Steinbach, Christoph; Schmidt-Posthaus, Heike; Šálková, Eva; Kolářová, Jitka; Vojs Staňová, Andrea; Grabic, Roman; Randák, Tomáš (Chemosphere, 2020)
Methamphetamine, mainly consumed as an illicit drug, is a potent addictive psychostimulant that has been detected in surface water at concentrations ranging from nanograms to micrograms per litre, especially in Middle and East Europe. The aim of this study was to expose brown trout (Salmo trutta fario) to environmental (1 μg L-1) and higher (50 μg L-1) concentrations of methamphetamine for 35 days with a four-day depuration phase to assess the possible negative effects on fish health. Degenerative liver and heart alterations, similar to those described in mammals, were observed at both concentrations, although at different intensities. Apoptotic changes in hepatocytes, revealed by activated caspase-3, were found in exposed fish. The parent compound and a metabolite (amphetamine) were detected in fish tissues in both concentration groups, in the order of kidney > liver > brain > muscle > plasma. Bioconcentration factors ranged from 0.13 to 80. A therapeutic plasma concentration was reached for both compounds in the high-concentration treatment. This study indicates that chronic environmental concentrations of methamphetamine can lead to health issues in aquatic organisms.
Keywords: chemické látky znečišťující vodu; Evropa; Europe; pstruh; methamfetamin; Kidney; Water Pollutants, Chemical; Animals; Liver; Methamphetamine; játra; ledviny; zvířata; Trout